2019
DOI: 10.1088/1755-1315/388/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding some medical plants on some productive performance traits of Japanese Quail.

Abstract: This study was conducted in the field quail of the Agriculture College/University of Basrah for the period from 24/11/2018 to 04/01/2019 to study the effect of adding different levels of dietary Marjoram (Origanumvulgarae) and (Rosmarinus officinalisL) on some productive of Japanese Quail in the study (450) chick. Unsexed one day old chicks were used at an initial weight 8.5 g. The chicks were randomly distributed into Ten treatments each treatment contained 45 chicks with three replicates each one has 15 chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Recently, Mossa et al (2019) showed that medicinal plants are widespread in poultry feed as antibiotics alternatives. Several studies also confirmed the beneficial effects of phytogenic additives on growth performance, nutrient retention, gut health, intestinal microflora, reduced susceptibility to diseases, enhanced immunity function, and improved carcass yield and quality in poultry (Ashour et al 2014;Ashour et al 2020aAshour et al , 2020bAshour et al , 2020c.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Mossa et al (2019) showed that medicinal plants are widespread in poultry feed as antibiotics alternatives. Several studies also confirmed the beneficial effects of phytogenic additives on growth performance, nutrient retention, gut health, intestinal microflora, reduced susceptibility to diseases, enhanced immunity function, and improved carcass yield and quality in poultry (Ashour et al 2014;Ashour et al 2020aAshour et al , 2020bAshour et al , 2020c.…”
Section: Introductionmentioning
confidence: 99%
“…Marjoram is a medicinal plant belongs to the oral family that plays an important role in inhibition of cancer cells and removal of free radicals through its antioxidant activity (Keck and Finley 2004), The Rosemary is a medicinal plant that acts as an anti-microbial and anti-inflammatory agent as it has the cathese (Peter 2004). Similarly adding marjoram leaves powder, rosemary leaves powder and their mixture in feed on the productive qualities of Japanese quail (Mossa et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Herbs have great potential to replace antibiotic growth promoters because they have antimicrobial, coccidiostat and anthelmintic-like pharmacological properties that may potentially improve growth performance by optimizing feed intake and gut health (Cruz Martínez et al 2017;Lee et al 2021;van Wietmarschen et al 2022;Chen and Si-Yong 2022;Anyaegbunam et al 2022). Herbs also favor beneficial bacteria and influence gastric secretion which improve gut health (Mossa et al 2019;de Macedo et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies performed to increase the efficiency of feed utilization of rabbits, which consequently improve the growth rate and the immunity to achieve more efficient financial profitability (Perić and Lukić, 2009). Recently, Mossa et al (2019) found that medicinal plants are widespread in rabbit feeds as antibiotics alternatives. (Ashour et al, 2014), observed that many studies confirmed the beneficial nutrient retention, gut health, intestinal micro-flora, reduced susceptibility to diseases, enhanced immunity function and improved carcass yield and quality in poultry production.…”
Section: Introductionmentioning
confidence: 99%